Strategy Strategy to Increase the Competitiveness of Palembang City MSMEs Post Covid 19 - Sopian Sopian; Fretty Welta (International Journal of Economics, Business and Innovation Research, 2024)
Community emporment is an acivity increasing community participation ini fulfillment life’s needs and solving problems experienced by society. The results show a response positive government and active community participation tall. The aim of this activity is to promote and improve product quality in order to achieve more develop and be able to compete with the MSME industry during the Covid 19 pandemic. In order to improve empowerment and welfare of the community through entrepreneurship to become an independent society and develop through branding and product marketing to promising business opportunities, because there are many interested by many groups.